Estudio comparativo del nivel de empatía en los estudiantes de la Facultad de Ciencias de la Educación, Humanas y Tecnologías de la Universidad Nacional de Chimborazo, Riobamba – Chimborazo, periodo abril – agosto 2018 - Rivadeneira Villa, Juan Pablo (2019)
The present research was developed centrally in a comparative study of the level of empathy in the students of the Faculty of Education, Humanities and Technology Sciences of the National University of Chimborazo, in which the general objective was to determine the levels of empathy and compare in the students of said faculty and university mentioned above, where the main beneficiaries were the 294 students who were the primary subjects when this research was carried out; It was carried out by means of a psychometric test. Empathy Test of Lucrecia Persian, which points out three levels of empathy (high, medium and low) with 30 questions; these results were obtained: 71 male students, 30 students with a high level of empathy, 40 students with a medium level of empathy and 1 student with a low level of empathy; 223 female students of which 137 students with a high level of empathy, 86 students with a level of average empathy; concluding that female students are more empathetic for the different reasons found in this research compared to students of the male gender.